Wordwall Media in Learning Pancasila Education on Learning Outcomes and Learning Motivation for Fifth Grade Elementary School Students - Zahwa Iftithaa Russhaimah; Teguh Supriyanto; Tri Murtini (Universitas Pendidikan Ganesha, 2024)
The current problem is that learning activities must be aligned with the desired learning outcomes. Some activities do not use digital learning media, so students need learning assistance. Based on this, this research aims to test the effectiveness of word wall media in class V elementary school on student motivation and learning outcomes. This type of research is quantitative research. The design used in this research was quasi-experimental, with a sample of 59 class V students consisting of 27 control class students and 32 experimental class students taken using random sampling techniques. Data collection was carried out by researchers using test techniques, questionnaires, and documentation in the control class and experimental class. The data collection instrument is in the form of test questions. Hypothesis testing in this research starts by testing the prerequisites for analysis with normality and homogeneity tests. After fulfilling the requirements, proceed with the Independent and One Sample T Test. The research results show differences in student learning outcomes after implementing word wall media in learning Pancasila education material. It was concluded that wordwall media effectively improved learning outcomes and motivation for fifth-grade elementary school students. The research implies that the application of Wordwall media can help overcome student learning problems and improve student learning outcomes.